Fusion of hard and soft control strategies for the robotic hand - Chen, Cheng-Hung; Naidu, D. S. 1940- (IEEE Press : Wiley, 2017)
An in-depth review of hybrid control techniques for smart prosthetic hand technology by two of the world's pioneering experts in the field Long considered the stuff of science fiction, a prosthetic hand capable of fully replicating all of that appendage's various functions is closer to becoming reality than ever before. This book provides a comprehensive report on exciting recent developments in hybrid control techniques--one of the most crucial hurdles to be overcome in creating smart prosthetic hands. Coauthored by two of the world's foremost pioneering experts in the field, Fusion of Hard and Soft Control Strategies for the Robotic Hand treats robotic hands for multiple applications. It begins with an overview of advances in main control techniques that have been made over the past decade before addressing the military context for affordable robotic hand technology with tactile and/or proprioceptive feedback for hand amputees.- Resumé vydavatel
Obsahuje index.
Keywords: biomedicínské inženýrství; robotika; protetika; biomedical engineering; robotics; prosthetics; robotické ruce; monografie; elektronické knihy; monographs; electronic books